Pastoral Literature; An Effort to Form an Environmental Love Character - Rahman, Hasrul (Universitas Hamzanwadi, 2021)
Pastoral Literature is a literary theory that offers an environment as a database in a literary work. Currently, the environment is a part of human life that is starting to lose its sustainability. The method used in this study is a qualitative descriptive method with reading and note-taking techniques. The results of this study indicate that the spotlight on the environment always comes when a natural disaster occurs, after the disaster has passed the spotlight weakens again so that this problem has no solution. The concept of pastoral literature has a very important role for learning in schools. Pastoral literature is one of the characteristic forms of literary ecocriticism. The selection of pastoral literature is solely to focus students more on instilling a love for the environment. Because ecocriticism has a wider scope.Kata Kunci: Pastoral Literature, Environment, Novel